PEMETAAN PERSEPSI KONSUMEN MUSLIM TERHADAP E-COMMERCE BERBASIS SYARIAH; ANALISIS DESKRIPTIF DAN VISUALISASI HEATMAP - Mustofa Mahfudz Fauzi; Jaharuddin Jaharuddin (Taksasila Edukasi Insani, 2026)
The rapid growth of digital technology has transformed consumer behavior in Indonesia, particularly in online shopping activities. E-commerce has become one of the most dynamic sectors of the digital economy, yet challenges such as product mismatches, delivery delays, and data security concerns continue to undermine consumer trust. For Muslim consumers, religiosity plays a crucial role in shaping perceptions of digital services, emphasizing values such as halal transactions, honesty, and avoidance of riba. This study adopts a quantitative descriptive-exploratory approach to map Muslim consumers’ perceptions of service quality, trust, satisfaction, religiosity, and loyalty toward sharia-based e-commerce platforms in Jabodetabek. Data were collected from 228 respondents through purposive sampling and analyzed using descriptive statistics, complemented by heatmap visualization. Findings reveal that consumers highly value convenience and accessibility, while concerns remain regarding data security. Trust is primarily driven by platform reputation, satisfaction is influenced by emotional comfort, and religiosity strongly reinforces consumer preferences for halal and ethical transactions. Loyalty emerges as a strategic outcome of consistent service quality and alignment with Islamic values. The novelty of this study lies in its descriptive mapping of consumer perceptions using heatmap visualization, offering practical insights for platform managers and providing a conceptual foundation for future causal research in sharia-based digital commerce.Keywords: Sharia-based e-commerce, Muslim consumer perception; service quality,trust,satisfaction, religiosity, loyalty, heatmap visualization. (times new roman 12, spasi 1, cetak miring).